UMK - ECER : agropolitan project - initiatives in alleviating hardcore poverty - Ahmad Anwar Mohamed Ismail; Mohd Badrul Hisyam Muhamad Alias; Faiz Nur Hakim Azmi (2012)
The east coast states of Malaysia, namely Kelantan, Terengganu and Pahang are usually considered to be left behind in the mainstream development of the national economy. To address this incongruence, where tradisionally the west coast states in the peninsula are far more developed, the goverment has taken the initiative in setting up an ambitious Regional Development Plan referred to as the East Coast Economic Region (ECER). Universiti Malaysia Kelantan (UMK) as a public university was given the task to spearhead the development of the region. From 2009, UMK working jointly with the ECERDC (East Coast Economic Region Development Council) has initiated and implemented various programmes with the objective of changing the mind set of the hardcore poor. The Agropolitan projects is an integrated socioeconomic project initiated by ECERDC with the aim of eradicating poverty among the hardcore poor communities within the region. A key feature of the project was the allocation of land for agriculture activities such as livestock farming (Dorper), oil palm cultivation and aquaculture. It also invovles secondary activities such mushroom production, sweet corn cultivation, handicraft making, aqua and hydroponics that help to supplement the income of participants.Through these activities, participants were capable of generating a steady monthly income ranging from RM1,000 to RM 2,000. Sinar ECER Programme is another initiative of ECERDC in which UMK was involved primarily. This educational programme was targeted to children of between 6 and 12 years old whose parents were the participants of the Agropolitan project. it was held to teach them the basic living skills and to provide knowledge with the ultimate goal of promoting academic excellence, as well as to develop positive mindsets and character buildup among the children. Besides the two main programmes, UMK has also organized a number of short hands-on training courses related to agriculture such as those on rearing and breeding of leeches, mushroom cultivation, worm composting and growing of rock melon and chili using fertigation which also include participants of the Agropolitan Project. The implementation of all these activities under the Agropolitan Project has seen a tangible impact on the participants whether it was from the heads of the household or members of the family. The same module will futher be evaluated and improved for implementation on the participants of the Agropolitan Project in the phase. However, the success of this programme is entirely dependent on close monitoring and supervision at all levels for those who implement it on the ground.